2016
DOI: 10.1111/pbr.12447
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐assisted selection for rice blast resistance genes Pi2 and Pi9 through high‐resolution melting of a gene‐targeted amplicon

Abstract: The use of host resistance (R) genes is considered the most cost‐effective option to control the rice blast disease. The two allelic R genes Pi2 and Pi9 confer very broad‐spectrum resistance against blast isolates collected worldwide. However, the two genes have not yet been widely deployed in rice breeding programmes. Availability of specific markers for them would facilitate incorporating the two R genes into new rice lines through marker‐assisted selection. Herein, we report the development and utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It implied that the two-gene pyramid R504 can reach the resistance effect of the three-gene pyramid R507. Indeed, it is inevitable to bring more genomic compositions from the DPs into the RP to produce three-gene pyramid than two-gene pyramid in the same procedure (Luo et al 2017). Eventually, it is confirmed that R507 exhibited low RP genome recovery and differences on more traits from RP as compared to R504.…”
Section: Discussionmentioning
confidence: 99%
“…It implied that the two-gene pyramid R504 can reach the resistance effect of the three-gene pyramid R507. Indeed, it is inevitable to bring more genomic compositions from the DPs into the RP to produce three-gene pyramid than two-gene pyramid in the same procedure (Luo et al 2017). Eventually, it is confirmed that R507 exhibited low RP genome recovery and differences on more traits from RP as compared to R504.…”
Section: Discussionmentioning
confidence: 99%
“…It could also create new source of resistant germplasm for enhanced blast resistance breeding in rice. Though pyramiding of multiple blast R genes and their alleles using molecular breeding has been successfully used in rice but there are no reports on stacking of multiple major rice blast R genes or alleles using co-transformation approach in an indica rice line (Xiao et al 2016;Fukuoka et al 2015;Khanna et al 2015;Das and Rao 2015;Luo et al 2017). Most of the studies used marker assisted selection (MAS) for crop improvement and MAS is found to be associated with linkage drag.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Pi33 located on the short arm of chromosome 8, showed resistance to > 2000 isolates originating from 55 countries (Berruyer et al 2003). MAS and conventional breeding together have facilitated the mentioned above broad-spectrum R genes to be incorporated in elite rice varieties to improve their blast resistance and durability (Deepti et al 2017), especially Pigm , Pi2 and Pi9 at Piz locus to overcome blast diseases in rice has been successfully demonstrated (Jiang et al 2015; Luo et al 2017). However, due to high variability and emergence of new virulent races in the M. oryzae population, R genes such as Pi9 , Pi5 and Pi3 (t) may loss broad-spectrum resistance to the pathogen populations when deployed individually (Variar et al 2009).…”
Section: Introductionmentioning
confidence: 99%